Algebraic Reasoning of Students with Logical-mathematical Intelligence and Visual-spatial Intelligence in Solving Algebraic Problems - Putri Ekawaty Kobandaha; Yusuf Fuad; Masriyah Masriyah (SAINTIS Publishing, 2019)
This study aims to describe the algebraic reasoning of students with logical-mathematical Intelligence and visual-spatial Intelligence in solving algebraic problems. This research is a qualitative descriptive study. The subjects of this study were students of eighth grade students of junior high school totaling 35 students. The results of the research data were analyzed by describing the algebraic reasoning of students with logical-mathematical Intelligence and students with visual-spatial Intelligence on each of the defined indicators. Data collection techniques are carried out by tests, observation, interviews, and documentation. The results showed that the student with logical-mathematical Intelligence and visual-spatial Intelligence in pattern seeking indicators, were able to identify, represent what was known and asked in the problem and find the constituent elements of the pattern. In the pattern recognition indicator students with logical-mathematical Intelligence find a relationship between elements and the similarity of the relationship of each element by thinking about it and accompanied by logical reasons. Students with visual-spatial Intelligence find a relationship between elements and the similarity of relations between each element by conducting experiments by writing down each process completely. In the generalization indicator, students with logical-mathematical Intelligence and students with visual-spatial Intelligence are able to model the situation or problem given and solve it correctly, and they are able to find a general rule that can be used to solve problems.